Quantification of licit and illicit drugs on typical police station work surfaces using LC-MS/MS. Issue 2 (24th November 2016) - Doran, Gregory S.; Deans, Ralph M.; De Filippis, Carlo; Kostakis, Chris; Howitt, Julia A.
Abstract : Licit and illicit drug use is widespread in the community and as a result, drug residues can be transferred onto handles and work surfaces in shared places. Abstract : Licit and illicit drug use is widespread in the community and as a result, drug residues can be transferred onto handles and work surfaces in shared places. Police officers are more likely than members of the public to encounter drug residues while performing their work duties. As a result, sampling and analysis methodology must be developed to assess their work environments to determine which drug residues are present, at what concentration, and how long they may persist on the work surface to attempt to determine whether the residues pose a risk. The following reports a method for determining residues on work surfaces using cotton swabs, solvent extraction and analysis with LC-MS/MS. LC column type, swab extraction time, solvent composition, and analyte suppression were investigated. The reported method is simple, allows high throughput at low cost, simultaneously analyses for 23 licit and illicit drugs and metabolites, and has the scope for inclusion of additional analytes. Additionally, the method could be adapted easily to suit other organic chemicals, such as pesticides. The optimised method was used to investigate the persistence of 23 drugs and metabolites on five different surface types commonly found in police stations, under both dark and illuminated incubation conditions. The results demonstrated that different drugs within a given class can have dramatically different rates of loss, and general predictions cannot be made for other drugs in the same class. Illuminated incubation conditions generally accelerated the loss of drugs on surfaces, either by enhanced volatilisation, photocatalysis, or a combination of both. Only drugs such as amphetamine, methamphetamine and ketamine deviated from this trend because their disappearance from all surfaces under both incubation conditions was so rapid that no real difference was observed.